2019
DOI: 10.1016/j.jappgeo.2019.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the bulk and shear moduli of soil surrounding a plastic water pipe using measurements of the predominantly fluid wave in the pipe

Abstract: Leak noise correlators are commonly used to detect and locate leaks in buried water pipes. They use the cross-correlation function between leak noise signals measured using hydrophones or accelerometers placed on the pipe either side of the leak. The efficacy of a correlator is dependent upon knowledge of the speed at which the leak noise propagates along the pipe as well as how much it attenuates with distance. The leak noise is carried in a predominantly fluid-borne wave in the pipe, which is heavily influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Note, that the effects of the soil and the pipe properties on the bandwidth over which leak noise is measured is not discussed here, as this has been treated in refs. [8,16,19].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Note, that the effects of the soil and the pipe properties on the bandwidth over which leak noise is measured is not discussed here, as this has been treated in refs. [8,16,19].…”
Section: Discussionmentioning
confidence: 99%
“…6. In this test-rig, the pipe system and the pipe diameter are much smaller than the other two test-rigs and the surrounding soil is very stiff clay [19]. The measurements were made over 5.5 m, which is a much shorter distance than in the other cases, so the bandwidth in which leak noise is found to be much higher, 273 746 − Hz.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, accurate evaluation in-situ acoustic properties of soils, especially wave speed, plays a significant role in the seismic wave method [101,102] and pipe leakage detection [143], as wave speed is directly related to the interpretation of measurement results. Therefore, many studies have been conducted on measurement of soil properties, which can be found in [144][145][146][147][148].…”
Section: Soil Propertymentioning
confidence: 99%